Characterization of Polymer Composites between Stereocomplex Polylactide Blends with Poly (methyl methacrylate) - Onpreeya Veang-in; Yottha Srithep; John Morris; Dutchanee Pholharn (Materials Science, 2022)
Polylactide stereocomplex (ST) of poly(L-lactide) (PLLA) and poly(D-lactide) (PDLA) (PLLA:PDLA 50:50) was blended with poly(methyl methacrylate) (PMMA) 10 – 50 wt.%. The materials were dissolved in chloroform at room temperature and the films were then cast. Differential scanning calorimetry showed a stereocomplex melting peak at 208 °C – 50 °C higher than that for neat PLLA or PDLA - confirming the polylactide stereocomplex crystallites. The PMMA content ratio of 10 – 50 wt.% in the stereocomplex showed almost complete stereocomplex crystallites. A peak at about 908 cm-1 in Fourier transform infrared spectra further confirmed the stereocomplex crystallites which indicated that PMMA could blend and efficiently bond with the stereocomplex. The X-ray diffraction analysis showed that the stereocomplex crystallinity became smaller when PMMA was added. Morphology from scanning electron microscopy revealed that phases separated in the ST/PMMA blend when the amount of PMMA was increased. Adding PMMA to stereocomplex films led to an increased elongation at break which peaked at 30 % added PMMA. Increased PMMA also led to the improved thermal stability of the stereocomplex. These properties and higher toughness are also needed in common applications, in particular films for packaging and protection of manufactured products.
Keywords: biodegradable polymer synthesis and properties; Carbon dioxide utilization in catalysis